2020
DOI: 10.1002/pa.2236
|View full text |Cite
|
Sign up to set email alerts
|

The nexus of workplace incivility and emotional exhaustion in hotel industry

Abstract: Workplace incivility is continuously seen as a stressor for the employee and the organization. No organization prospers in an uncivil environment. The high level of turnover intention that results from an uncivil working environment threatens the organization's reputation and sustainability. Adopting from Bagozzi's Appraisal‐Emotional Response, this study tested the relationship between workplace incivility, turnover intention, and job satisfaction via the mediating role of emotional exhaustion, using AMOS ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 122 publications
(221 reference statements)
3
29
0
Order By: Relevance
“…The current study shows that there is a positive impact of perceived organizational politics on emotional exhaustion. Moreover, Workplace incivility significantly affects emotional exhaustion (Alola et al, 2020;Hur et al, 2016;Karatepe et al, 2019;Peng et al, 2016;Rahim & Cosby, 2016;Tong et al, 2019). The mediation adds novelty for this study as workplace incivility was a mediator of perceived organizational politics on emotional exhaustion.…”
Section: Discussion Of Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…The current study shows that there is a positive impact of perceived organizational politics on emotional exhaustion. Moreover, Workplace incivility significantly affects emotional exhaustion (Alola et al, 2020;Hur et al, 2016;Karatepe et al, 2019;Peng et al, 2016;Rahim & Cosby, 2016;Tong et al, 2019). The mediation adds novelty for this study as workplace incivility was a mediator of perceived organizational politics on emotional exhaustion.…”
Section: Discussion Of Resultsmentioning
confidence: 69%
“…A study conducted by Makhdoom et al (2017) expounded that there is a significant impact of perceived organizational politics on the workplace incivility of high school teachers at private and government schools. Furthermore, there were previous studies conducted and investigated that workplace incivility significantly affects emotional exhaustion (Alola et al, 2020;Hur et al, 2016;Karatepe et al, 2019;Peng et al, 2016;Rahim & Cosby, 2016;Tong et al, 2019). However, there is a lack of studies on this area in the apparel sector.…”
Section: Perceived Organizational Politics Workplace Incivility and Emotional Exhaustionmentioning
confidence: 99%
“…In other words, management should consider both supervisor incivility and coworker incivility as equally serious matters, and it is important to reflect them in training programs. Also, it is desirable to administer training programs for all employees without exception given that workplace incivility has strong negative consequences for both employees and organizations (Alola et al , 2020; Jawahar and Schreurs, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Two of the main consequences that have received particular attention in the literature are OCB and turnover intentions. Specifically, it has been consistently found that witnessing rudeness and other uncivil behaviors corrodes employees’ citizenship behavior and negatively predicts turnover intentions (Alola et al , 2020; Chen and Wang, 2019; Porath and Erez, 2009; Karatepe et al , 2019; Mahfouz et al , 2017; Rahim and Cosby, 2016; Tricahyadinata et al , 2020).…”
Section: The Research Modelmentioning
confidence: 99%
“…That is, it expands knowledge about employees' well-being. To date, the scarce previous studies analyzing the mediating role of emotional exhaustion between job demands and employees' work attitudes report mixed results (Alola et al , 2020; Hang-Yue et al , 2005; Hur et al , 2015; Kemp et al , 2013). Specifically, emotional exhaustion may lead employees to establish lower emotional bonds and a greater desire to leave the organization, which can negatively influence the service quality, level of responsibility assumed, prospects for promotion, variety of tasks undertaken or choice of more appropriate working methods.…”
Section: Introductionmentioning
confidence: 99%